Influence of COVID-19 on social media usage: association with mental well-being in undergraduate students - Yang, Zhan; Gray, Sophie; Sparkes, Maggie; Hack-Polay, Dieu; Zhou, Bin (Frontiers in Education, 2025)
ObjectiveDuring the COVID-19 pandemic, social media usage was rapidly accelerated by increased social isolation due to public health measures that attempted to limit the spread of the virus. Even though numerous studies indicate that increased screen usage during the pandemic is associated with negative mental health outcomes, there is no consensus on the effect of social media apps on mental health. This study investigated the impact of COVID-19 on the mental health of students attending a privately funded Christian university on their social media usage.MethodsThe data used for this study were collected using a cross-sectional survey involving 36.5% of the full-time undergraduates in the traditional Art Business and Science (ABS) undergraduate program at a privately funded Canadian Christian university.FindingsConsistent with previous research, an increase in social media use and its detrimental impact on people’s mental health during COVID-19 that we identified indicates that social media greatly impacts undergraduates’ lives. COVID-19 aggravated social media usage in student groups with a lower mental health status. Nevertheless, moderate social media use on specific social platforms can promote mental health against social isolation and stress generated by the pandemic. In the post-COVID era, the residual pandemic impact was higher for participants with low mental health status. Furthermore, during the pandemic, religion appeared to be a protective factor against excessive screen use on social media.OriginalityThis study examined the use of social media in a Christian university context and highlighted the effect of religion on the screen time of social media among students. To the best of our knowledge, this is the first such study.